P026: Need for training in medical education: staff emergency physician perspectives. (15th May 2017) - Bryan, J.; Al Rawi, F.; Bhandari, T.; Chu, J.; Hansen, S.; Klaiman, M.Z.
Abstract : Introduction: Emergency medicine physicians in our urban/suburban area have a range of training in medical education; some have no formal training in medical education, whereas others have completed Master's level training in adult education. Not all staff have a university appointment; of those who are affiliated with our university, 87 have appointments through the Department of Medicine, 21 through the Department of Pediatrics, and 117 through the Department of Family Medicine. Emergency physicians in our area are a diverse group of physicians in terms of both formal training in adult education and in the variety of settings in which we work. The purpose of this study was to gauge interest in formal training in adult education among emergency medicine physicians.Methods: With research ethics board approval, we created and sent a 10-item electronic questionnaire to emergency medicine staff in our area. The questionnaire included items on demographics, experience in emergency medicine, additional post-graduate training, current teaching activities and interest in short (30-60 minute) adult education sessions.Results: Of a potential 360 active emergency physicians in our area, 120 responded to the questionnaire (33.3%), representing 12 area hospitals. Nearly half of respondents had been in practice over 10 years (48.44%). Respondents were mainly FRCP (50%) or CCFP-EM (47.50%) trained. 33.3% of respondents had masters degrees, of which 15% were MEd. Most physicians were involved in teaching medical students (98.33%), FRCP residents (80%) and family medicine residents (88.3%), though many were also teaching off-service residents, and allied health professionals. More than half of respondents (60%) were interested in attending short sessions to improve their skills as adult educators. The topics of most interest were feedback and evaluation, time-efficient teaching, the learner in difficulty, case-based teaching and bedside teaching.Conclusion: Emergency physicians in our area have a wide variety of experience and training in medical education. They are involved in teaching learners from a range of training levels and backgrounds. Physicians who responded to our survey expressed an interest in additional formal teaching on adult education topics geared toward emergency medicine.